Pelatihan Pola Asuh Anak Remaja di Kelurahan Limus Nunggal - Hartono, Hartono (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2023)
Adolescent parenting training is one solution to the problems faced by parents and children, namely the lack of understanding of juvenile delinquency and proper parenting for adolescents. The purpose of this activity is to increase understanding among parents and children about juvenile delinquency and proper parenting for adolescents. The method of implementing this activity is training for parents and children in the Limus Nunggal Village environment. The partner in this training activity is Limus Nunggal Village Village. The evaluation was carried out by giving questionnaires to trainees before and after the delivery of the material, and the result was that the comprehension ability of the participants increased by 40%.